Effect of a generalized shape Peierls potential and an external stress field on kink mechanism in a continuum model. (March 2017) - Pi, Z.P.; Fang, Q.H.; Liu, B.; Liu, Y.; Wen, P.H.
Abstract: The a 0 / 2 〈 111 〉 screw dislocation glides through the nucleation and propagation of the kink-pair which dominates the plastic deformation of the BCC iron. A continuum model and the corresponding numerical methods are developed to investigate the kink mechanism on an arbitrary shape Peierls potential and subject to an external stress field. This model gives a link between the Landau theory of phase transitions and the line tension theory of string models. The order parameter is associated with the screw dislocation in BCC iron for describing the relative slip between adjacent Peierls valley. The kink configurations on the different Peierls potentials, such as the sinusoidal, Eshelby, anti-parabolic and camel-hump potential, are derived. By considering the motion of the screw dislocation on a 2-D Peierls potential surface, the 3-D saddle-point configuration of a non-planar kink-pair is obtained. The configuration is directly related to the details of the 2-D potential surface and it changes along with the applied stress tensor. A parameterized constitutive equation is derived for describing the temperature dependence of the flow stress which is compared with the experimental data from literature. The twinning/anti-twinning (T/AT) asymmetry and the tension-compression (T/C) asymmetry are reproduced in the model. The results rule out the possibility that the non-Schmid plasticity of the BCC iron is ascribed to split configuration. Highlights: The continuum model provides a link between Landau theory of phase transitions and line tension theory of string models. The kink configurations on the different Peierls potentials are derived. The non-Schmid plasticity of the BCC iron is associated with the 3-D saddle-point configuration of the 〈 111 〉 110 / 2 screw dislocation. The result rules out the possibility that the split configuration can be used for explaining the non-Schmid law.